Describing the deformation behaviour of TRIP and dual phase steels employing an irreversible thermodynamics formulation - Li, S.; Honarmandi, P.; Arróyave, R.; Rivera-Diaz-del-Castillo, P. E. J. (Materials science and technology, 2015)
The plastic deformation of multiphase steels is described employing an irreversible thermodynamics formulation. Transformation induced plasticity and dual phase grades are described within a single theoretical framework. The approach describes the plastic deformation of each individual phase in terms of the evolution of dislocation density, subject to dissipative mechanisms associated to dislocation generation, glide and annihilation. The collective behaviour of the ensemble of phases into a single microstructure is ensured through a self-consistent approach based on the iso-work approximation. The parameterised model shows very good agreement with several alloys studied experimentally and available in the literature.